Peningkatan Mutu Pendidikan Keagamaan dan Karakter pada Kalangan Anak Usia Sekolah di Desa Girimekar - Karlina, Susi; Al-Amin, Muhammad Insan (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2022)
The importance of character and religious education among school-age children plays an important role in the growth and development of children because at school age, children’s brain growth is very rapidly developing and their time is very eager to know many things. In Girimekar Village, the development of character and religious education is facilitated by the existence of Madrasah Taklimiyah Diniyah (MDT) Khalasha for elementary school to high school children, then Raudhatul Athfal (RA) Khalasha for children aged 4-6 years. The role of MDT and RA in Girimekar village RW 05 is very important for the people there, because MDT and RA Khalasha are the center for the development of character and religious education there. In addition to religious knowledge, MDT and RA Khalasha also balance it with other sciences. From the survey results that have been carried out, the children there are very fond of studying religion and other sciences, they are also very interested in knowing many things. And from the results of the survey itself, the children there more often study religious knowledge because Girimekar Village itself is a santri village, besides that they also like to learn new things. Therefore, character and religious education in Girimekar village is very important for the future of the children there. This dedication is also motivated by the lack of educational development there, especially education other than religious